Pendampingan Pengelolaan Desa Wisata Watu Kandang untuk Mengembangkan Potensi Lokal Wisata Alam di Desa Pandean Kabupaten Trenggalek - Seftiani, Tika; Nusantara, Widya (J+PLUS UNESA, 2023)
The purpose of this study is to analyze and describe how the process of assisting the management of tourism villages in Pandean Village, the development of natural tourism potential that exists after the program is carried out and what factors influence the process in it. This research uses descriptive qualitative methods. The results showed several stages of assistance, namely (1) Planning through action shows, socialization, filtering and deliberation, (2) Implementation through field sharing, understanding SOPs, training, mock studies, exhibitions and family talks, (3) Monitoring and evaluation through, partner independence, and joint meetings. The mentoring activities carried out succeeded in developing the potential of natural tourism which was initially in a damaged condition and had no value to become the main attraction for Pandean Village. Furthermore, the supporting factors of the mentoring activities are the strong cooperation and cohesiveness between Pokdarwis as the mentoring team and the Pandean community as the target group. Meanwhile, the inhibiting factors of mentoring activities are negative opinions from outsiders aimed at the existence of the program and miscommunication between managers.